Perceived Value as a Predictor of Behavioral Intention Mediated by Customer Engagement and Customer Satisfaction Sanding Waterboom Bandung Regency - Komala, Dewi; Ernawadi, Yadi (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
This study aims to examine the influence of perceived value comprising functional value, epistemic value, social value, economic value on behavioural intention with customer engagement and customer satisfaction serving as mediating variables in the context of Sanding Waterboom a tourist destination in Bandung Regency. Expectation Confirmation Theory (ECT) is employed as the underpinning theory within the scope of artificial tourism. The study involved 140 respondents who had previously visited Sanding Waterboom. Data were collected using a cross-sectional approach and the research instruments underwent rigorous validity and reliability testing. The data were analysed using Structural Equation Modeling with SmartPLS software version 3.0. All proposed hypotheses were empirically supported. The findings indicate that perceived value exerts a positive influence on behavioral intention through customer engagement and customer satisfaction. This study makes a significant contribution to marketing literature by introducing epistemic value as a key antecedent of customer engagement. The novelty of this study lies in the addition of a hypothesis establishing a relationship between epistemic value and customer engagement. Future research is encouraged to explore other variables such as conditional value as potential drivers of behavioral intention particularly by aligning these variables with the unique attributes of the objects under investigation.